Discontinuous transitions to collective dynamics in star motifs of coupled oscillators - Santos, Edmilson Roque dos (2018)
This dissertation is dedicated to the rigorous study of discontinuous transitions in star graphs of coupled phase oscillators. A star graph consists of a central node, called hub, connected to peripheral nodes called leaves. We consider the setting where the frequency of the leaves is identical and the hub has a higher frequency when isolated. This captures the effect of positive correlation between the hub high number of connections and its high natural frequency. Hub higher frequency turns out to be the key feature for discontinuity in the transition from incoherent to synchronous behavior. This transition has been observed numerically and explained via a non-rigorous analytical treatment in the thermodynamic limit. Using Möbius group reduction and the theory of persistence of normally hyperbolic invariant manifold, we prove that this transition is indeed discontinuous for a certain set of initial conditions.